Disease-specific suppressive granulocytes participate in glioma progression - Jiarui Zhao; Di Wu; Jiaqi Liu; Yang Zhang; Chunzhao Li; Weichen Zhao; Penghui Cao; Shixuan Wu; Mengyuan Li; Wenlong Li; Ying Liu; Yingying Huang; et al. (Cell Reports)
Summary: Glioblastoma represents one of the most aggressive cancers, characterized by severely limited therapeutic options. Despite extensive investigations into this brain malignancy, cellular and molecular components governing its immunosuppressive microenvironment remain incompletely understood. Here, we identify a distinct neutrophil subpopulation, termed disease-specific suppressive granulocytes (DSSGs), present in human glioblastoma and lower-grade gliomas. DSSGs exhibit the concurrent expression of multiple immunosuppressive and immunomodulatory signals, and their abundance strongly correlates with glioma grades and poor clinical outcomes. Genetic disruption of neutrophil recruitment in immunocompetent mouse models of gliomas, achieved through Cxcl1 knockout in glioma cells or host-specific Cxcr2 deletion or diphtheria toxin A-mediated neutrophil depletion, can significantly enhance antitumor immunity and prolong survival. Further, we reveal that the skull bone marrow and meninges can be the primary sources of neutrophils and DSSGs in human and mouse glioma tumors. These findings demonstrate a critical mechanism underlying the establishment of the immunosuppressive microenvironment in gliomas.